SAMDHYA: The Time of Prayer and the Prayer of time - Malieckal, Louis (Journal of Dharma, 1985)
Alexis Carrel, the Nobel Prize winner in medicine says that prayer is the most powerful form of energy one can generate. "It is a force." he says. "as real as terrestrial gravity." Prayer like radium, he adds, is a source of luminous self-generating energy and when we pray we link ourselves with inexhaustible moving power that spins the universe.' Probably never before in the living memory of mankind was this cosmic dimension of prayer felt more vividly by the world at large than when America's Apollo thirteenth manned space mission to the moon, ended up in a tragic failure some years ago. In spite of the advanced scientific knowledge and computer technology available at tl1::11time, the lives of the three men on board the space-ship-James Lowell, Fred Hais and John Swigert+-were seriously at stake due to some irreparable technical snag which developed at some point during the onward flight. And then the hearts of men and women the world over rose as one, praying for their safe return. Instances of prayer coupled with penance and sacrifice during the anxious and agonizing hours of human existence, regardless of nation, religion and ideology, are too numerous to quote. Somehow a 'miracle' happened, in the case of Apollo and after their safe return what John Swigert, one of the space crew, said to the crowd of media reporters amply testifies to this. He said : "If you are ask- ing me whether I prayed, yes certainly I did; and I have no doubt that my prayers and the prayers of the rest of the world did an awful lot for us getting back."